Analisis Perencanaan Persediaan Bahan Baku Biji Plastik LDPE (Studi Kasus : CV. Jaya Perkasa Abadi) - Christian Steve Jonathan Mundung; Siti Mundari (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
CV. Jaya Perkasa Abadi is a company that specialises in the production of cast buckets using LDPE (Low Density Polyethylene) pellets as raw material. CV. Jaya Perkasa Abadi is located at Pergudangan Jaya Park Blok C No. 7 Dusun Kapas Melati, Jabaran Village, BalongBendo District, Sidoarjo Regency. This company faces challenges in managing the supply of LDPE (Low Density Polyethylene) seed raw materials, which are subject to fluctuations in demand. The fluctuation in demand leads to excess and shortage of plastic pellet raw material stock. To overcome this problem, it is necessary to analyse the planning and management of the supply of LDPE (Low Density Polyethylene) seed raw materials using the probabilistic calculation method of the P back order model. This method involves iteration to select the best solution resulting in the minimum total inventory cost. Based on the calculation results using the P back order model probabilistic calculation method. The most optimal results were obtained with a total cost of Rp 5,693,109,330 by placing orders T_0 every 6 days or 0.018 years, the expected maximum inventory is 14.441 kg and the service level is 99.99%.